2010
DOI: 10.1117/1.3432750
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of ultrasound and different-concentration glycerol–induced changes in human skin optical attenuation assessed with optical coherence tomography

Abstract: Abstract. Previous studies have demonstrated the ultrasound-induced skin optical clearing enhancement with topical application of 60% glycerol ͑G͒ on in vitro porcine skin and in vivo human skin. Our purpose was to find the relation between the effect of optical skin clearing and different concentrations of glycerol and to find more effective ultrasound-glycerol combinations on optical skin clearing. The enhancement effect of ultrasound ͓Sonophoresis ͑SP͒ delivery͔ in combination with 40% G, 60% G, and 80% G o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…The low-frequency US effect (sonophoresis) is one of the noninvasive methods of improving the clearing effect for many OCAs, increasing the depth and rate of their delivery into tissues [134,135,[165][166][167][168]. The combined use of OCA and US provided considerable increase of the depth and contrast of the OCT images of porcine skin in vitro and human skin in vivo [166].…”
Section: Immersion Clearingmentioning
confidence: 99%
See 2 more Smart Citations
“…The low-frequency US effect (sonophoresis) is one of the noninvasive methods of improving the clearing effect for many OCAs, increasing the depth and rate of their delivery into tissues [134,135,[165][166][167][168]. The combined use of OCA and US provided considerable increase of the depth and contrast of the OCT images of porcine skin in vitro and human skin in vivo [166].…”
Section: Immersion Clearingmentioning
confidence: 99%
“…Beside the chemical agents, a number of physical methods of surmounting the skin barrier are proposed to enhance the diffusion, including low-and high-intensity irradiation [130,158], fractional lamp [131,133] and laser [132] microablation, mechanical microperforation [137,138], ultrasonic (US) irradiation [134,135,159], electrophoresis [160], needleless injection [161], mechanical removal of the surface layer by means of abrasive paper [136], epidermal stripping [162], and microdermabrasion [163].…”
Section: Immersion Clearingmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of them are overviewed in Refs. 3, 4, 11-17 and recent ones present optical clearing of tissues such as skin, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] sclera, [33][34][35] and skeletal muscle. [36][37][38][39][40][41] We have found that only in two papers optical clearing of heart tissues were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, the diffusion of immersion agents into the skin is hindered by the existence of epidermal barrier. To overcome the barrier function of the epidermis, different methods are used, including the chemical dissolving of the lipid layer [5,6], the mechanical damages [7], the effect of ultrasound [6][7][8][9], etc. Among these methods, the laser microablation of epidermis can be used to solve the problem.…”
Section: Introductionmentioning
confidence: 99%